Preparing Teacher Training Students for Evidence-Based Practice Promoting Students’ Research Competencies in Research-Learning Projects - Böttcher-Oschmann, Franziska; Groß Ophoff, Jana; Thiel, Felicitas (Frontiers in Education, 2021)
Research-learning projects (RLP) enable teacher training students to acquire competencies for evidence-based practice (EBP) in the context of their university studies. The aim of this longitudinal study is to develop, implement, and evaluate a RLP format to promote competencies for EBP in teacher training students. These competencies can be broken down into the categories of using research, which involves reflection on and use of evidence to solve problems in teaching practice, and establishing research, which involves investigating a research question independently by applying research methods. In a longitudinal study we evaluate the increase in competencies based on a self-assessment of competencies (indirect measurement) focusing on establishing research, and a competence test (direct measurement) focusing on using research. We also add a retrospective pre-assessment version (quasi-indirect measurement) to consider response shift and over- or underestimation in self-assessments. Our findings show that teacher training students can be prepared for EBP through RLP. Further development potential for the RLP format is being discussed.